Model of Islamic Wealth Management Based on Maqasid al-Shariah - Isma Swadjaja; Tjiptohadi Sawarjuwono; Unti Ludigdo (Journal of Innovation in Business and Economics, 2019)
Islamic wealth management has been aimed at choosing investment instruments so that their portfolios get maximum returns. The process of wealth management emphasizes wealth accumulation without linking it with Maqashid al-Shariah, such as how to safeguard assets (hifz al-mal), protecting assets oriented to offspring (hifz al-nasl) and so on. The orientation is on welfare in the world without involving elements of blessing and the pleasure of Allah SWT. This study uses a qualitative method through the postmodernism approach. First, the reconstruction of the model is associated with relevant values in Maqashid al-Shariah. Second, the researcher makes observations on the actions and thoughts of investors in interpreting investment and managing investment returns by shariah in the capital market. Third, applying the Islamic wealth management model based on Maqashid al-Shariah according to the results of the study. The output of this study is a model of asset management based on Maqashid al-Shariah as a grand theory in shariah stock investments in the capital market, to achieve the ultimate goal of prosperity in the world and the hereafter and provide positive benefits for all parties.